2019
DOI: 10.1093/ejo/cjz012
|View full text |Cite
|
Sign up to set email alerts
|

Survival probability of dental autotransplantation of 366 teeth over 34 years within a hospital setting in the United Kingdom

Abstract: Summary Introduction The purpose of this retrospective study was to evaluate 34 years’ experience of autotransplantation of teeth during orthodontic treatment. Methodology Treatment was completed at Queen Mary’s Hospital, Sidcup, Kent, UK, during the period 1969–2003. A total of 366 teeth were transplanted in 314 patients. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…By keeping the natural teeth versus any kind of prosthetic replacement, there was potential for induction of further alveolar bone growth and maintenance of a normal periodontal ligament to support proprioceptive function, along with maintenance of the interdental papillae, giving a more optimal aesthetic result [8]. Furthermore, as autotransplanted teeth have the potential to erupt alongside neighbouring teeth during continued facial growth of the patient, this is also a good option in younger patients who are still growing [13]. Autotransplantation has been a useful technique that has been performed with good outcomes [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By keeping the natural teeth versus any kind of prosthetic replacement, there was potential for induction of further alveolar bone growth and maintenance of a normal periodontal ligament to support proprioceptive function, along with maintenance of the interdental papillae, giving a more optimal aesthetic result [8]. Furthermore, as autotransplanted teeth have the potential to erupt alongside neighbouring teeth during continued facial growth of the patient, this is also a good option in younger patients who are still growing [13]. Autotransplantation has been a useful technique that has been performed with good outcomes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as autotransplanted teeth have the potential to erupt alongside neighbouring teeth during continued facial growth of the patient, this is also a good option in younger patients who are still growing [13]. Autotransplantation has been a useful technique that has been performed with good outcomes [13]. In their retrospective study, Abela et al reported that apical pathology was seen in 16% of autotransplanted teeth post-operatively with the majority of cases being evident in the first 3 years [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of an open apex, an immediate root canal treatment should not be performed, so that a follow-up can be carried out and the root may nish forming without showing signs or symptoms of infection. Root canal treatment is needed only when there are radiological signs of resorption or periapical pathology [15]. If the root canal treatment is necessary, it should be performed prior to transplantation or 15 days after.…”
Section: Prognostic Factors and Successmentioning
confidence: 99%